Design and optimization of Frequency Selective Surfaces (FSS) - Luo, Xingfang (2008)
The analysis method for Frequency Selective Surfaces (FSS), the spectral-domain Method of Moments (MoM) is improved to be applicable to normal incidence. A more efficient optimization algorithm, Differential Evolution Strategy (DES) is proposed to optimize the standard, non-irregular FSS unit-cell and dielectric properties. DES coupled with spectral-domain MoM is proposed to design arbitrary FSS structures especially with multi-layered hexagon and gangbuster array. DES combined with Equivalent Circuit Model (ECM) is proposed to design double-square, gridded-square and gridded-double-square array for multi-band application. The DES is applied to optimize the dimensions and dielectric properties of FSS dipole array. The frequency response of FSS screen is analyzed by employing spectral-domain MoM or ECM technique. The tedious trial and error procedure is avoided.